Human behavior in organizations - Vandeveer, Rodney C. (Prentice Hall, 2010)
In this book, readers are introduced to the foundations of Organizational Behavior through the self-discovery of their own personalities, preferences, abilities, and learning styles. The concepts of individual, group, and organizational behavior are delivered in a way that allow readers to envision how they will fit into organizations and be successful in leadership roles. A variety of tools are used to guide the reader through the self discovery process, including chapter opening self-assessment tests, chapter opening and closing case studies and the Prentice Hall Self-Assessment Library.